Expression of HER4 isoforms and HER4 localisation in HER2 negative breast cancer cell lines - Ali, Nursyazana Aqilah (2021)
Breast cancer is the most common cancer-affecting women with the most common subtype is HER2 positive breast cancer. Patients with HER2 positive breast cancer are treated with Herceptin, a monoclonal anti-HER2 antibody that is proven to improve survival. Unfortunately, the incidence of primary or acquired resistance to Herceptin remains a challenge for an effective treatment. The overexpressions of HER family receptors such as HER1, HER3 and HER4 are one of the mechanisms of Herceptin resistance. Among the HER family receptors, the role of HER4 in breast cancer is uncertain where some reports suggest a tumour suppressive function while others suggest an oncogenic function. The conflicting role of HER4 is due to the presence of different isoforms and nuclear translocation of HER4. In this study, we investigated the expression of HER4 isoforms and its localisation in HER2-negative cell lines, MCF-7 and MDA-MB 231. The expression of HER4 isoforms (CYT-1, CYT-2, JM-a and JM-b) was determined by qRT-PCR, while nuclear and cytoplasmic localisation of HER4 was determined by western blot. There is a variability of HER4 isoforms expressions in between the MDA-MB-231 (HER2-/ER+/PR+) and MCF-7 (HER2-/ER+/PR+). Nuclear and cytoplasmic HER4 were highly expressed in MCF-7 cells than MDA-MB 231. High expressions of HER4 isoforms and HER4 localisations in MCF-7 that have positive ER expression may suggest a possible association of HER4 and ER in mediating the mechanism of anti- HER2 resistance. In future, understanding on the role of HER4-ER interaction in anti-HER2 resistance is warranted.